KONDISI KEAIRAN SUMBER AIR PANAS PARANGWEDANG DI DAERAH PARANGTRITIS KECAMATAN KRETEK KABUPATEN BANTUL DAN ARAHAN PENGEMBANGAN UNTUK PARIWISATA - -, Miftahussalam (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
The objective of research is to determine the inundated condition of Parangwedang Hot Spring Resources and provide to support tourism development. Methods of research was conducted by field research, source water sampling of Parangwedang Hot Springs and laboratory analysis.Lithology of study area is composed by Tertiary volcanic rocks, carbonaceuos clastic sediments and Quarternary alluvial deposits. Based on hydrogeological condition, known that study area has potential hot spring water. Based on geological analysis, and the study of Parangwedang Hot Spring known that resources is a remnant of palaeomagmatism during Tertiarry. In the basis of physics, chemistry and limited microbiology analysis, Parangwedang Hot Spring might be applied to toursm development, such as thermal baths. In order Parangwedang Hot Spring Resources to be a main tourist destination in Parangtritis area, the government of Bantul Regency should be improved to promote it and collaborate with their sponsorship, in increasing its tourism management.